The mediating role of cognitive test anxiety on the relationship between academic procrastination and subjective wellbeing and academic performance - Albulescu, Ion; Labar, Adrian-Vicenţiu; Manea, Adriana-Denisa; Stan, Cristian (Frontiers in Public Health, 2024)
Background Promoting wellness as a predictor of sustainable development empowers schools to model healthy behavior. The multiple interactions in real and virtual environments that today's youth are subjected to force schools to explore effective educational strategies to provide a quality education for students and their families. Purpose This study examines the relationship between academic procrastination, assessment anxiety, subjective wellbeing, and academic performance. Methods A convenience sample of 322 undergraduate students () was used, and questionnaires were administered to students measuring academic procrastination, cognitive test anxiety, and subjective wellbeing. For the same target group, the level of academic performance was identified using personal reports. The questionnaires were administered between May and June 2023 in an online format. For the data analysis, we applied correlational analysis and path analysis using. Results Both test anxiety and academic procrastination negatively correlate with performance and subjective wellbeing, leading to decreased performance and subjective wellbeing. Procrastination correlates positively with test anxiety. Cognitive test anxiety partially mediated the relationship between academic procrastination and subjective wellbeing and fully mediated the relationship between academic procrastination and academic performance. Thus, high procrastination leads to decreased performance and subjective wellbeing both directly and indirectly through increased test anxiety, leading to decreased performance and subjective wellbeing. Significance/discussions As a result of theoretical and practical investigations, it emerges that joint action of educational actors is required in the generation of effective educational strategies for the prevention and control of procrastination and evaluation anxiety, given the fact that both a high level of procrastination as well as assessment anxiety led to the decrease of students' wellbeing, to the registration of low academic performances. In the long term, disruptive behavior (procrastination and anxious behavior) could generate low social and professional performance, which is a research question for a future longitudinal study.